SISTEM PENYEDIAAN DAN PENGENDALIAN KUALITAS PRODUK IKAN SEGAR DI HYPERMARKET - Tri Wiji Nurani; Julia Eka Astarini; Marina Nareswari Astarini (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2011)
Fresh  sh product is one food that is offered in Giant Hypermarket. Supply system and quality control of products is important to ful l consumer’s need and satisfaction. The study was aimed to examine the supplysystem and quality control of fresh  sh products at Giant. The analysis method used were the ABC analysis, singleexponential smoothing method, p control charts, and diagrams of causation. The results of this study indicatethat fresh  sh products must be controlled properly by the Giant, these include banana prawn and shrimp small pancet which were categorized as product A. The budget available for product A reached is Rp1,158,979,112 or 73.7% of the total inventory cost and reached 2,394.24 kg or 8% of the total supply of seafood per year. The single exponential smoothing method with parameter smoothing (α) 0.9; was considered as the best parameter to be used for estimate supply of banana prawn, in the year 2010. The proportion of banana prawn that is not ful lled quality standard is still under control. Such condition is expected can be maintained and improved fresh  sh quality by the Division of Seafood Giant by considering the factors in uencing the product quality control system which include human, technology, materials, and handling methods aspects.Keywords: fresh  sh products, Giant Hypermarket, quality control, supply system, single exponential smoothing,